(untitled) (Journal of the College of Basic Education, 2022)
When our Arabic language was strong, our nation was strong; And when our nation weakened, the use of our language became weak, hence the nation was the language and the language is the nation... It is noticeable that the higher the nations, the more they depend on the language, and this is not evidenced by the fact that books, newspapers and other written materials are more quantity and variety in the developed nations Some of them are among the backward nations (14: 12-13).One of the facts that cannot be ignored is that every nation that cherishes itself and its existence must cherish its language, and that every human language has characteristics that distinguish it from others.